DEVELOPMENT AND EVALUATION OF MUCOADHESIVE MICROSPHERES OF HYDROCORTISONE SODIUM SUCCINATE IN THE TREATMENT OF CHRONIC SINUSITIS - BANSAL, RUCHI; KAUSHIK, DINESH; JAIN, SAROJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: In the world, chronic sinusitis is one of the most common illness disorders. However, no viable medication has been identified to fully cure it as of yet. Patients are necessitated to use sprays, inhalers, and other devices to treat chronic sinusitis in contrast to all of its dangerous symptoms. However, these dosage forms need for concurrent administration, which cause inconvenient in the long term. An effort has been made to create a controlled release dosage form to increase patient compliance. Methods: Two polymers Chitosan and HPMC were used to create hydrocortisone sodium succinate microspheres through the orifice-ionic gelation process. Result and Discussion: It had a yield of about 89.33±2.33% drug entrapment efficiency and 86.65±0.25% percentage yield. The evaluation results for formulation F6 were the best of all the formulations. Conclusion: It concluded that the most effective and promising dosage form was microspheres made from the drug (hydrocortisone sodium succinate), sodium alginate, and HPMC in the ratio of 1:2:2.